Serum Albumin as a Potential Predictor of Pneumonia after an Acute Ischemic Stroke - Yang, Xue; Wang, Lu; Zheng, Lukai; Wu, Jiongxing; Liu, Junfeng; Hao, Zilong; Zhang, Shihong; Wu, Bo; Liu, Ming; Wang, Deren (Current neurovascular research, 2020)
Serum albumin level is associated with infection after stroke, but whether albumin predicts post-stroke pneumonia is unclear. The potential relationship between albumin level and pneumonia in patients with acute ischemic stroke (AIS) was evaluated in this study. A consecutive sample of 798 AIS patients who were admitted to West China Hospital within 24 h after onset, from the year 2017 to 2018, were retrospectively analyzed. Blood was collected on admission and assayed for serum albumin. Univariate analyses, multivariate logistic regression, and stratified logistic regression were performed to identify the risk factors of post-stroke pneumonia. Out of the 798 patients, 240 (30.2%) developed pneumonia at a median of 48 h after onset (interquartile range, 27-74 h). Patients with pneumonia had significantly lower serum albumin levels than those without pneumonia (40.6 vs. 42.9 g/l, p<0.001). After adjustment, the albumin level was still significantly associated with pneumonia in multivariate logistic regression (odds ratio [OR] 0.87, 95% confidence interval [CI] 0.81-0.94). The association between serum albumin and pneumonia tended to depend on National Institutes of Health Stroke Scale score (p = 0.045), but this was significant only in patients with mild stroke (OR 0.84, 95% CI 0.77-0.93). A dosedependent inverse relationship was found between albumin levels and the risk of pneumonia after AIS. Albumin values predicted pneumonia with an area under the curve of 0.661 (95% CI 0.620- 0.701), and the optimal cutoff was 42.6 g/L. Low serum albumin levels may be independent predictors of pneumonia in patients with AIS, especially in mild stroke. In fact, the risk of pneumonia may vary inversely with albumin level.